PENGARUH CARA PENGERINGAN SIMPLISIA TERHADAP KADAR FENOLIK DAN AKTIVITAS TABIR SURYA EKSTRAK ETANOL 70% DAUN CINCAU HIJAU (Cyclea barbata Miers.) - Rusmawati, Lisa; Rahmawan Sjahid, Landyyun; Fatmawati, Sofia (Media Farmasi Indonesia, 2021)
Extract cincau leaves green according to previous studies have the value of the antioxidant IC50 49,45±0,64 µg/mL. According to researchers the phenol formerly produced through a method of drying oven with higher than the drying with sunlight and dried use wind. The research aims to understand the influence of means drying simplisia against phenolic levels total and the activity of a natural sunscreen on extract ethanol 70 % cincau leaves green (Cyclea barbata Miers). Drying simplisia in research is divided into three which is drying with the dry wind, the sun, and an oven. Green leaves cincau simplisia extracted by using the method maceration. Testing the phenolic committed using the folin ciocalteu method. The determination is based on the SPF value Mansur. The results of the value of phenolic or on the program have managed to extract by the difference means drying simplisia dry wind, the rays of the sun and an oven respectively namely 32,7089; 46,2500 and 59,5500 mgGAE / g. The SPF value obtained from each extract with different methods of drying simplisia showed significant differences in various concentration test.